A Pigmented Cyst in the Anterior Vitreous of a 4-year old Child: Case Report - Neves Cruz, Carlos (2021)
Vitreous cysts are a rare and mostly accidental finding. We report a case of a 4-year-old male without a relevant medical history who resorted to a routine ophthalmology consultation. On ophthalmological examination, he had a 6/10 (Snellen decimal scale) best corrected visual acuity in both eyes. Biomicroscopy showed a pigmented and rounded lesion (3 mm of larger diameter), located in the anterior vitreous of the left eye, that moved with eye movements. Besides this lesion and the shadow-effect it produced in the retina, there were no other changes in fundus examination. Associated inflammatory/infectious pathologies were excluded. At 6-month and 1-year follow-up, no new symptoms or morphological changes of the lesion were found. The etiology of vitreous cysts is diverse, requiring a thorough study and close follow-up in order to decide the most appropriate approach.